Comparative Feasibility Studies of High Voltage Circuit Breaker Operating in the LFAC System With Different Frequencies - Wen Wang; Keli Gao; Zhibing Li; Xianglian Yan (IEEE Access, 2022)
With the development of the flexible low frequency transmission technology following the improvement of offshore wind power transmission, it is of great significance to investigate the operation adaptability of the main equipment especially under the low frequency conditions. A comparative study was performed in the present work to discuss the dynamic operation performance of a 252 kV/50 kA puffer-type circuit breaker influenced by the system operational frequency. Since the decreased operational frequency would result in a longer arc duration, a pre-designed driving mechanism with characteristics of high speed control was proposed and compared with a conventional unit. Moreover, as one of the reasonable indicators to evaluate the interruption performance of the circuit breaker, the critical rate of rise of recovery voltage (RRRV) that the circuit breaker can withstand after the arc extinguishment under different low frequencies were computationally obtained by an established arc model. The effects of the frequency change on the arc dynamic characteristics during the interruption of circuit breaker were comprehensively discussed as well and it could reasonably provide technical optimisation for the development of low-frequency-based circuit breaker for further engineering applications by analysing its interruption feasibility.